2009
DOI: 10.1007/s00382-009-0640-6
|View full text |Cite
|
Sign up to set email alerts
|

Key features of the IPSL ocean atmosphere model and its sensitivity to atmospheric resolution

Abstract: International audienceThis paper presents the major characteristics of the Institut Pierre Simon Laplace (IPSL) coupled ocean-atmosphere general circulation model. The model components and the coupling methodology are described, as well as the main characteristics of the climatology and interannual variability. The model results of the standard version used for IPCC climate projections, and for intercomparison projects like the Paleoclimate Modeling Intercomparison Project (PMIP 2) are compared to those with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
237
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(241 citation statements)
references
References 77 publications
2
237
0
2
Order By: Relevance
“…The land-use used is fixed at its present day value for all simulations. The forcing that we have used for our experiments in terms of climate results from two coupled ocean atmosphere climate experiments using the IPSL_CM4 model [Marti et al, 2010]. The atmosphere component of this coupled model is LMDZ.3.3 [Hourdin et al, 2006], with a resolution of 96 × 72 × 19 points in longitude × latitude × altitude.…”
Section: Methods and Model Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The land-use used is fixed at its present day value for all simulations. The forcing that we have used for our experiments in terms of climate results from two coupled ocean atmosphere climate experiments using the IPSL_CM4 model [Marti et al, 2010]. The atmosphere component of this coupled model is LMDZ.3.3 [Hourdin et al, 2006], with a resolution of 96 × 72 × 19 points in longitude × latitude × altitude.…”
Section: Methods and Model Descriptionsmentioning
confidence: 99%
“…To our knowledge, this is the first time that this method is applied to comprehensively analyze the causes of the global runoff evolution for this period. In the first simulation, the ORCHIDEE land surface model [Krinner et al, 2005] is forced with the observed 20th century CO 2 evolution and 21st century IPCC A2 CO 2 scenario and by the corresponding climate evolution simulated by the IPSL coupled ocean atmosphere model [ Marti et al, 2010]. We first validate the results using data from the 20th century, then we attribute the runoff trend over 20th and 21st centuries and analyze the differences between these two periods.…”
Section: Introductionmentioning
confidence: 99%
“…The mean oceanic state has been described in Marti et al (2010) in a version using slightly different resolutions and parameters, and in Escudier et al (2013) for the present IPSL-CM5A-LR version. The Gulf Stream is too broad because of the coarse horizontal resolution and its position is too equatorward because of the bias in the zonal wind stress (see Fig.…”
Section: B Coupled Model Evaluationmentioning
confidence: 99%
“…The sea-ice component is LIM2 (Louvain Ice Model, Fichefet and Morales-Maqueda 1997), which resolves three layers (one for snow and two others for seaice) and accounts for sea-ice dynamics. The model is described in more detail in Marti et al (2010), but this version includes the marine carbon cycle model PISCES (detailed below). The IPSLCM4 is a fully coupled climate and carbon cycle model (Cadule et al 2010).…”
Section: Ipsl-cm4-loopmentioning
confidence: 99%
“…This biogeochemical model further includes a representation of the iron cycle and limitation by multiple nutrients (Aumont 2003;Schneider et al 2008). Additionally, in the three selected Earth System Models, each of the ocean circulation models is based on the same code, although versions differ as to resolution and subgrid-scale physics (Madec 2008a, b;Marti et al 2010;Voldoire et al 2012;Dufresne et al 2012). The largest differences in simulated ocean circulation fields probably stem from each ocean model being coupled to a different atmospheric model.…”
mentioning
confidence: 99%